A revision of male ants of the Malagasy region (Hymenoptera: Formicidae): Key to genera of the subfamily Dolichoderinae - Yoshimura, Masashi; Fisher, Brian L. (Zootaxa, 2011)
Keys to the males of the Dolichoderinae ant genera known from the Southwest Indian Ocean islands (Comoros, Madagascar, Mauritius, Mayotte, Reunion, and Seychelles) are provided. Diagnoses, discussion, illustrations, and a character matrix are provided for all five extant genera from the region: Aptinoma, Ochetellus, Ravavy, Tapinoma, and Technomyrmex. A male-based synopsis of the subfamily Dolichoderinae based on the five genera is also given. The previous diagnostic characters for the included genera are reconsidered. Terminologies for male genitalia and wing cells are reviewed.